Confucianism and Same-Sex Marriage - Bai, Tongdong (Politics and religion, 2021)
In the majority opinion by the U.S. Supreme Court over same-sex marriage, a claim by Confucius was quoted, which led to an uproar among Confucian scholars in mainland China. In this article, I will first explain the background of the debate over same-sex marriage in the United States, and why Confucius's claim was quoted. I will then show how a contemporary Confucian philosopher Zhang Xianglong addressed the issue of same-sex marriage from a Confucian perspective. In my view, compared with other mainland Confucians' responses, Zhang's are one of the most scholarly and moderate responses that nevertheless follow Confucian values. But he eventually rejected same-sex marriage on the Confucian ground. I will argue that, based on some Confucian values and principles which are shared by Zhang, we can answer Zhang's concerns with same-sex marriage, thus offering an even more moderate Confucian stance that accepts same-sex marriage. But this stance is still different from the typical liberal one. We will also see that, in order to accept same-sex marriage, it is the liberals, not the Confucians, who will have to deal with an issue—the acceptance of polygamy—that poses a serious challenge to the principle of equality, which is fundamental to some liberals.